Analysis of the Influence of Unemployment and Poverty Levels on Economic Growth in West Sumatra Province in 2017-2021 - Putra, Argo Beba; Illahi, Ilham (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2023)
The background of this research is that unemployment and poverty have fluctuated from 2017-2021, while economic growth has decreased from 2017-2020 and has increased in 2021. This situation was triggered by the unstable state of economic development in West Sumatra Province. In this economic development, the concept of economic growth emerges which is a process of changing the economic conditions of a region to lead to a better state. Economic growth is influenced by various factors, such as unemployment and poverty. This study aims to prove empirically and see whether unemployment and poverty rates affect economic growth. The method used is associative quantitative and the data comes from BPS with a 5 year time series. partial research results, namely the unemployment rate (X1) does not have a negative effect on economic growth (Y) so that H0 is accepted and Ha is rejected. Meanwhile, poverty (X2) has a negative effect on economic growth (Y) so that H0 is rejected and Ha is accepted. Simultaneously, the unemployment rate (X1) and poverty (X2) have a negative effect on economic growth (Y), so that H0 is rejected and Ha is accepted.